Functional Outcomes with Primary Total Knee Replacement in Respect to Body Mass Index - Saddam Mazar; Imtiaz A Hashmi; Muhammad Sohail Rafi (Pakistan Journal of Medicine and Dentistry)
Background: Osteoarthritis (OA) is a prevalent condition and the leading disability among the elderly. Obesity, linked to a sedentary lifestyle, increases the risk of OA. Knee Osteoarthritis has improved functional outcomes after Total Knee Replacement (TKR). This study aimed to determine the functional outcomes of primary TKR based on BMI.